Амбивалентно - эквилибраторное действие слабоминерализованных кремниевых вод на показатели водно-солевого обмена у жнвотных с моделью экспериментального предиабета - Алексеенко, Н.А.; Дмитриєва, Г.А.; Гуща, С.Г. (Медична гідрологія та реабілітація, 2005)
In the experiment on white rats with the model of pre-diabetes changes of water-salt exchange and their correction by internal course introduction of low-miniralization of silicic waters is grounded .